270 The discordance between patient and physician perception of the disease: the paradigm of SLE. (April 2019) - Elefante, Elena; Tani, Chiara; Ferro, Francesco; Stagnaro, Chiara; Parma, Alice; Carli, Linda; Signorini, Viola; Mosca, Marta
Abstract : Background: Background: a discordance exists between patient and physician perspective in the evaluation of SLE and it may negatively impact on patient care. Our purpose was to compare patient and physician evaluation of the disease in a monocentric cohort of SLE patients, analyzing factors that influence patient perception. Methods: Methods: this is a cross-sectional study that enrolls adult patients with a diagnosis of SLE (ACR 1997 criteria). For each patient, demographics, comorbidities, treatment history, clinical and laboratory data were collected. Disease activity was evaluated with the SELENA-SLEDAI score and organ damage with the SLICC/DI. At enrollment each patient completed the following PROs: SF-36, FACIT-F, LIT, SLAQ and BILD. The Spearman test has been used for linear correlation between continuous data. Results: Results: we included 223 adult SLE patients (97, 24% Caucasian, 91, 93% female, mean age 44, 9413, 17 years, median disease duration 13 years). Median SLEDAI at enrollment was 2 (IQR 0–4); 18, 22% of patients had SLEDAI >4; 49, 33% had SLICC/DI>0. 11, 8% of the cohort had a concomitant fibromyalgia. At enrollment, the most frequent active disease manifestations were articular (36/223) and hematological (33/223), while only 15 patients had active renal involvement. The median score of the SLAQ questionnaire was 11 (IQR 6–16). No correlation was found between patients self-evaluation of the disease and the physicians assessment: SLAQ and SLEDAI scores were not significantly correlated. Among active disease manifestations, only arthritis (p=0, 03) and skin involvement (p=0, 04) resulted significantly associated with higher SLAQ scores. Moreover, the SLAQ score resulted significantly influenced by fibromyalgia (p<0, 001): patients with fibromyalgia seems to overestimate SLE disease activity. Finally, while SLEDAI didnt show any correlation with PROs on HRQoL, higher SLAQ scores were strongly associated with a worst patient perception of QoL, fatigue and SLE impact, as expressed by SF-36, FACIT-F and LIT (table 1 ). Conclusions: Conclusion: differently from the physicians assessment, SLE patients evaluation of their disease is influenced by milder manifestations but with a heavy impact on daily functioning, like arthritis and fibromyalgia. Patients self-evaluation has a strong impact on their perception of health status and disease burden. The integration of patient-driven data to the traditional clinical evaluation may improve the management of SLE patients. Funding Source(s): Founding: INTEGRATE project (European Commission, 3rd Health Program, Proposal ID 769736)